Role of uric acid as a biomarker of cognitive function in schizophrenia during maintenance period - Yuan, Zelin; Liu, Huamin; Zhang, Xiaochun; He, Yong; Gu, Shanyuan; Mo, Dan; Wang, Shaoli; Huang, Zhiwei; Wu, Keyi; Zhou, Rui; Zhong, Qi; Huang, Yining; et al. (Frontiers in Psychiatry, 2023)
Background. Previous studies involving uric acid (UA) in some specialized disease populations have found that high UA is associated with enhanced patient function. The mechanism to explain this association may be that UA, an important antioxidant, exerts neuroprotective effects. Patients with schizophrenia (SCZ) have severe oxidative stress abnormalities, and cognitive impairment is a major obstacle to their rehabilitation. Only few studies have been conducted on UA and cognitive impairment in SCZ. This study aims to clarify the relationship between UA and cognitive impairment and explore whether UA could be used as a potential biological marker of cognition in SCZ during maintenance period. Methods. A total of 752 cases of SCZ during maintenance period from Baiyun Jingkang Hospital were included. Cognition was measured using the Mini-Mental State Examination scale. UA was measured using the Plus method. The participants were grouped on the basis of UA to evaluate the association of cognition with low-normal (3.50–5.07 mg/dL for men, 2.50–4.19 mg/dL for women), middle-normal (5.07–6.39 mg/dL for men, 4.19–5.18 mg/dL for women), high-normal (6.39–7.00 mg/dL for men, 5.18–6.00 mg/dL for women), and high (>7.00 mg/dL for men, > 6.00 mg/dL for women) levels of UA. Multiple logistic regression and linear regression models and restricted cubic spline (RCS) were utilized to evaluate the relationship. Results. UA was positively associated with cognitive function. Subgroup analyses showed that high UA was associated with enhanced cognition in participants with low anticholinergic cognitive burden (ACB). Conclusion. UA may be used as a simple objective biological indicator to assess cognition in SCZ during maintenance period